2015
DOI: 10.1017/s0007114515002457
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fate (absorption,β-oxidation and deposition) of long-chainn-3 fatty acids is affected by sex and by the oil source (krill oil or fish oil) in the rat

Abstract: The effects of krill oil as an alternative source of n-3 long-chain PUFA have been investigated recently. There are conflicting results from the few available studies comparing fish oil and krill oil. The aim of this study was to compare the bioavailability and metabolic fate (absorption, β-oxidation and tissue deposition) of n-3 fatty acids originating from krill oil (phospholipid-rich) or fish oil (TAG-rich) in rats of both sexes using the whole-body fatty acid balance method. Sprague-Dawley rats (thirty-six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 36 publications
(57 reference statements)
3
29
0
Order By: Relevance
“…Our findings of greater accumulation of 22:6n-3 and 22:5n-6 in female rat plasma are in general agreement with a variety of observations related to DHA tissue content in rats [25, 3740]. Similarly in human subjects, higher erythrocyte DHA levels were observed in women of childbearing age by Smit et al [17] and Magnusardottir et al [23], as well as in postmenopausal women after hormone replacement therapy [21, 22].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings of greater accumulation of 22:6n-3 and 22:5n-6 in female rat plasma are in general agreement with a variety of observations related to DHA tissue content in rats [25, 3740]. Similarly in human subjects, higher erythrocyte DHA levels were observed in women of childbearing age by Smit et al [17] and Magnusardottir et al [23], as well as in postmenopausal women after hormone replacement therapy [21, 22].…”
Section: Discussionsupporting
confidence: 92%
“…Some PUFA are specifically required for reproduction [104]. It has been reported that PUFA concentrations are higher in females than in males during pregnancy and there are some studies showing sex-specific effects for some PUFA in determining several outcomes [68][69][70][71][72][73][74]140,141]. Although this is still an emerging field, the promotion of research investigating sex-specific differences [142] could provide more information regarding sex-specific effects on gene*sex interactions in determining PUFA levels for a more personalized nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue in these meta-analyses is the lack of focus on potential sex-specific differences, as well as overall dietary pattern modulating PUFA interventions. Regarding sex, several human studies as well as research in animal models [66][67][68][69][70][71][72][73] have reported some differences between males and females on analyzing the PUFA effects on diverse cardiovascular risk phenotypes. However, more specific research remains to be done in order to better understand the potential differences.…”
Section: Introductionmentioning
confidence: 99%
“…Longer experiments in different types of animals to ensure fatty acid levels reach equilibrium and a comprehensive fatty acid analysis of blood lipids (plasma, erythrocytes, or leukocytes) and other tissues are needed. For further insight on absorption and metabolism of n-3 PUFA from glycolipids, intake and excretion measurements as well as tracer studies using isotope-labeled ALA are needed [39][40][41].…”
Section: Discussionmentioning
confidence: 99%